Anomalous right coronary artery from the pulmonary artery in a young infant with ventricular septal defect - Anil Kumar Singhi; Richard Hawker; Gary Sholler (Journal of Indian College of Cardiology, 2021)
We report a case of anomalous right coronary artery from pulmonary artery (ARCAPA), which is a very rare congenital coronary defect. It can be an isolated lesion or associated with congenital cardiac defects such as tetralogy of Fallot or shunt lesions in up to 40' of cases. The clinical presentation varies from asymptomatic to signs of myocardial ischemia, cardiac failure, and/or ventricular arrhythmia. The electrocardiogram can be normal in a significant fraction of the cases. The diagnosis of ARCAPA may be confirmed by cardiac catheterization, computed tomographic angiogram, and cardiac magnetic resonance angiogram. Reimplantation of anomalous coronary artery is the treatment of choice. In the current era, systematic preoperative screening by echo is recommended.